Resistência de clones de seringueira à infestação por ácaros - Vieira, Marineide Rosa [UNESP]; Martins, Gustavo Luís Mamoré; Scaloppi Junior, Erivaldo José (Instituto Agronômico de Campinas, 2013)
Calacarus heveaeFeres (Eriophyidae) and Tenuipalpus heveae Baker (Tenuipalpidae) can cause heavy defoliation of rubber tree plants. From the perspective of integrated pest management, resistant clones can be an important strategy. The objective of this work was to evaluate the resistance of rubber tree clones to the attack of mites, in an experiment carried out in Votuporanga, SP. The experimental design was a randomized blocks with eighteen treatments and three replications. The treatments were the clones PB 230, PB 243, PB 252, PB 294, PB 306, PB 311, PB 312, PB 314, PB 324, PB 346, PB 350, PB 355, IAC 56, IAC 302, IAC 328, IAC 334, Fx 3899 and RRIM 600. The evaluation of C. heveae and T. heveae populations was performed by counting mites and exuviae presence in six leaflets per plot. The defoliation levels were evaluated with a score scale, varying from 0 (no defoliation) to 4 (above 75% of defoliation). Based on the results, Fx 3899 clone is resistant through non-preference and/or antibiosis to C. heveae. The IAC 56 clone is less susceptible to defoliation caused by C. heveae and T. heveae infestation.

Calacarus heveae Feres (Eriophyidae) e Tenuipalpus heveae Baker (Tenuipalpidae) podem causar intenso desfolhamento em plantas de seringueira. Na perspectiva de implantação de manejo integrado de pragas, o uso de clones resistentes pode vir a ser uma importante estratégia de controle. O objetivo deste trabalho foi avaliar a resistência de clones de seringueira ao ataque desses ácaros em experimento conduzido em Votuporanga, SP. O delineamento experimental foi o de blocos casualizados com 18 tratamentos e três repetições, sendo que os tratamentos adotados foram: clones PB 230, PB 243, PB 252, PB 294, PB 306, PB 311, PB 312, PB 314, PB 324, PB 346, PB 350, PB 355, IAC 56, IAC 302, IAC 328, IAC 334, Fx 3899 e RRIM 600. As avaliações populacionais de C. heveae e T. heveae foram realizadas pela contagem em laboratório dos ácaros e exúvias presentes em seis folíolos por parcela. Os níveis de desfolhamento foram avaliados com uma escala de notas de 0 a 4, sendo 0 ausência de desfolhamento e 4 desfolhamento acima de 75%. Com base nos resultados pode-se concluir que o clone Fx 3899 é resistente a C. heveae por não preferência e/ou antibiose. O clone IAC 56 é menos suscetível ao desfolhamento provocado pela infestação de C. heveae e T. heveae.
Resistance of rubber tree clones to mite infestation
Keywords: Hevea brasiliensis; Calacarus heveae; Tenuipalpus heveae; Acari; Hevea brasiliensis; Calacarus heveae; Tenuipalpus heveae; Acari